Opportunities and challenges in field data validation and corroboration: Matching household survey data with project monitoring data in Ethiopia - Makhija, Simrin; Spielman, David J.; Abate, Gashaw T.; Bernard, Tanguy (International Food Policy Research Institute, 2019)
The application of digital tools to agricultural extension and advisory services has attracted considerable attention in recent years. Among the many advantages it offers is the ability to capture and analyze large amounts of data on farmers, their farms, crops, and fields; and the choices they make about input use, technologies, management practices, and marketing.